PENGHAMBATAN PEMASAKAN BUAH SRIKAYA (Annona squamosa L.) DENGAN SUHU RENDAH DAN PELAPISAN KITOSAN - Widya Mudyantini; Endang Anggarwulan; Puji Rahayu (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2015)
Annona squamosa L.is one of the perishable climateric fruit. The aims of this research were to study the ethylene levels, physiological and biochemical characters with application of temperatures and chitosan during storage. The research had been performed using Completely Randomized Design (CRD) with two factors, the variations in storage temperature (5°C, 15°C, 25°C) and the variation in chitosan (0%, 2%, 3%, 4%) with five replicates. The treatment of temperature 25°C and chitosan 0% was used as controls. The parameters observed included in respiration rate, weight loss, levels of ethylene, pigments, fruit hardness, ascorbic acid content and sugar reduction. Sugarapple fruit were taken from the same tree. The fruit were coated by chitosan and were stored at storage temperature. Observations were made in everyday until the controls were ripe. Data collected were analyzed using Anava followed byDMRTat 5% test level. The result showed that the combination of storage temperatures and chitosanconcentrationshadsignificant effect on the shelf life and quality of sugar apple fruit measured by several parameters. The treatments wereable to decrease weightloss and respiration rate, to maintain the content of water, the levels of sugar reduction, ascorbic acid content, the levels of a chlorophylls, b chlorophylls, total chlorophylls, and carotenoids were remained still high. The higher temperature is the lower the ethylene levels. The best combination treatment to extend the shelf life and to maintain quality of sugar apple fruit was chitosan 3% at temperatures 15°C.